Augmented reality‐enhanced navigation in endoscopic sinus surgery: A prospective, randomized, controlled clinical trial. Issue 4 (7th August 2020) - Linxweiler, Maximilian; Pillong, Lukas; Kopanja, Dragan; Kühn, Jan P.; Wagenpfeil, Stefan; Radosa, Julia C.; Wang, Jingming; Morris, Luc G. T.; Al Kadah, Basel; Bochen, Florian; Körner, Sandrina; Schick, Bernhard
Abstract: Objective: Endoscopic sinus surgery represents the gold standard for surgical treatment of chronic sinus diseases. Thereby, navigation systems can be of distinct use. In our study, we tested the recently developed KARL STORZ NAV1 SinusTracker navigation software that incorporates elements of augmented reality (AR) to provide a better preoperative planning and guidance during the surgical procedure. Methods: One hundred patients with chronic sinus disease were operated on using either a conventional navigation software (n = 52, non‐AR, control group) or a navigation software incorporating AR elements (n = 48, AR, intervention group). Incidence of postoperative complications, duration of surgery, surgeon‐reported benefit from the navigation system and patient‐reported postoperative rehabilitation were assessed. Results: The surgeons reported a higher benefit during surgery, used the navigation system for more surgical steps and spent longer time with preoperative image analysis when using the AR system as compared with the non‐AR system. No significant differences were seen in terms of postoperative complications, target registration error, operation time and postoperative rehabilitation. Conclusion: The AR enhanced navigation software shows a high acceptance by sinus surgeons in different stages of surgical training and offers potential benefits during surgery without affecting the duration of the operation or the incidence of postoperative complications. Level of evidence: 1b.